Ice cream sandwiches : 65 recipes for incredibly cool treats - Egan, Donna (Ten Speed Press, 2013)
"A sweet collection of 50 recipes for ice cream sandwiches from London's popular Buttercup Bake Shop. In this charming and prettily packaged book, the humble ice cream sandwich gets a modern makeover. Combining easy-to-make recipes for ice cream fillings--like chocolate, lemon, mascarpone, and mocha--with simple cookies in a variety of tempting flavors, The Ice Cream Sandwiches Book is the first cookbook dedicated to this favorite cool treat. From the classic (peanut butter and brownie, oatmeal and lemon cream) to the decadent (chocolate-dipped mint chip with sprinkles, snickerdoodles with caramel and butterscotch) to the sublime (pumpkin mascarpone, elderflower amaretto), this fun and colorful cookbook has a recipe for every occasion"--